A Neighborhood Search for a Multi-size Container Transportation Problem. Issue 3 (2015) - Funke, Julia; Kopfer, Herbert
Abstract: This paper considers the combined problem of routing containers of different sizes and scheduling trucks carrying the containers that have to be moved according to the container routing. In intermodal freight transport, containers are covering routes on their way for loading, transporting and unloading customers' cargo. Trucking companies have to deal with two different types of container hinterland transportation. Namely, complete container transportation requests, in which fully loaded containers have to be transported between customers and terminals, and incomplete container transportation requests, which consist of moving empty containers to and from either a storage place or a point they have to be (unloaded. For complete transportation requests, the points of origin and destination are definitely determined. On the contrary, for incomplete transportation requests either the point where to pick up or the point where to deliver an empty container is undetermined and, consequently, is a matter of optimization. In the presented matheuristic approach, we add mathematical programming techniques to a neighborhood search in order to solve the combined container routing and vehicle scheduling problem. The approach is implemented. Two different benchmark tests have been performed: one investigates the solution quality and the other one examines the applicability of the heuristic approach to input data having realistic size.